Utilization of Social Media in Living Qur’an Learning: An Analysis of Generation Z Students - Muhamad Zaenal Muttaqin; Safa Husayn Alrumayh; Sami Alkamil Muhammad Barkah (Tuah Foundation, 2026)
This study examines the use of social media in Living Qur’an learning among Generation Z students, aiming to understand how digital social interaction contributes to the teaching and understanding of Qur’anic teachings. Data were collected through questionnaires and narrative analysis from 203 Generation Z student active on digital social media. A qualitative approach was adopted, and analysis was guided by Marc Prensky’s Digital Learning Theory, danah boyd’s Social Media and Communication Theory, and Lev Vygotsky’s Social Constructivism, providing an interdisciplinary perspective on student engagement. Findings indicate that 48.7% of respondents acknowledged the significant influence of digital social media interactions on their Qur’anic understanding. This research contributes to the discourse on digital platform engagement, emphasizing cyberspace’s role in shaping Islamic comprehension. Limitations include sample homogeneity and the need for more diverse methodological approaches. Future studies are recommended to explore the thematic and contextual influence of social media more comprehensively to develop relevant, engaging, and impactful educational strategies.